Disabilitas Klien Pasca Stroke terhadap Depresi - Maria Magdalena Purba; Nang Randu Utama (Politeknik Kesehatan Tanjung Karang, 2019)
Stroke is one of the public health problems in the world. Stroke can cause disability and functional disorders. The incidence of stroke in Indonesia increased sharply to become the third leading cause of death after heart disease and cancer. This study aims to determine the level of disability of clients after stroke against depression. Observational analytic research design with a cross-sectional design, performed at dr. Doris Sylvanus Palangka Raya in the Neural Poly Room. The Barthel index instrument to measure the level of disability, and the Hamilton scale instrument (HDRS) to measure the level of depression. The population in this study were post-stroke clients with disabilities who went out to the neurology clinic of dr. Doris Sylvanus Palangka Raya Hospital in the period January-June 2017 as many as 58 clients after stroke, so that by using the Sugiyono formula the sample size in this study was 38 people. The results of the study showed a significant relationship between the age of the patients after stroke with the level of depression with a value of p-value=0,032 and with a level of disability with a value of p-value=0,006 (p-value<0,05), p-value=0,000 (p-value<0,05). The results of the analysis of the level of disability of patients after stroke against depression are shown with a value of p-value=0,018 (p-value<0,05). There is a significant relationship between the level of disability of patients post-stroke for depression. Health education is needed to improve disability and depression in post-stroke patients.